A computable general equilibrium modeling platform for the azorean economy : a simple approach with international trade - Bayar, Ali (2011)
Computable general equilibrium models have become commonplace instruments of economic policy analysis in many developed countries. These models have gained increased acceptance due to their capacity to address many policy questions in a simple way, using now commonly available databases on the structure of production in the form of input-output matrices, while retaining traditional economic assumptions for household, firm and government behaviour, among others such as trade. In this paper we lay –out the model for application to the Azorean economy. The model contemplates households, firms, government, and trade. It is calibrated using a SAM built from a 1998 I-O table with all information updated to 2001. The impact of changes in trade is analysed.